Explaining the green development behavior of local governments for sustainable development: evidence from China - Du, Jianguo; Zhu, Xiaowen; Li, Xingwei; Ünal, Enes; Longhurst, Philip J. (MDPI, 2023)
Although researchers have examined organizational sustainability practices, a specific interpretation of local government green development practices remains for supplemental analysis. This study conducted an empirical survey of 53 local officials from departments related to green development to understand the key processes and practices of green development behavior of local governments in China. The key findings indicate that the main stakeholders involved in the green development practices of Chinese local governments consist of enterprises and residents. In part, local government green development practices emphasize the greening of enterprises, especially in the step of process environmental regulation. The new institutionalism theory and the organizational process research provide dependable insights into green development behaviors. Our findings further shed light on the process of cross-sectoral cooperation across local government departments in green development, contributing to local multi-sectoral interactions for regional green development.
Keywords: local government; green development behavior; new institutionalism; organizational process research; grounded theory